Effect of deep brain stimulation on motor complications in Parkinson’s disease: a systematic review and meta-analysis - Xu, Hu; Wan, Xing; Tu, Qi; Chen, Huahui; Tong, Minfeng; Xu, Zhijian; Cai, Dandan (Frontiers in Human Neuroscience, 2025)
BackgroundDeep brain stimulation (DBS) significantly improves tremor, rigidity, bradykinesia, and dyskinesia for patients with Parkinson’s disease (PD), but gait and speech remain inconsistent. These discrepancies underscore the need for a systematic, quantitative synthesis of existing data to clarify the impact of DBS across different motor domains.ObjectiveTo systematically evaluate the effects of DBS on motor symptoms in PD by analyzing UPDRS-III scores and conducting subgroup analyses based on stimulation target, stimulation type, and medication status.MethodsA literature search was conducted to identify relevant studies on clinical trials and observational studies reporting pre- and post-DBS motor assessments in PubMed, Embase, the Cochrane Central Register of Controlled Trials (CENTRAL), Ovid MEDLINE, and Web of Science from inception to 15 December 2024.ResultsA total of 35 studies comprising 1,082 PD patients were included. The pooled analysis demonstrated a significant improvement in overall UPDRS-III scores post-DBS (WMD: = −1.09, 95% CI: −1.32 to −0.87, p < 0.05). Subgroup analyses showed consistent improvements across tremor, rigidity, akinesia, bradykinesia, dyskinesia, and axial symptoms, regardless of stimulation target or medication state. UPDRS Part IV scores also significantly improved, reflecting reduced motor complications. However, speech function remained unchanged, and UPDRS Part I scores initially showed no significant improvement, though significance emerged after removing sources of heterogeneity.ConclusionDBS significantly improves overall motor function, particularly tremor, rigidity, and bradykinesia. However, its effects on gait and speech remain inconsistent, which shows the need for further research to refine patient selection and optimize stimulation parameters. These findings provide valuable insights into the therapeutic impact of DBS in PD management.